Max Weber's Sociology of Religion - Adair-Toteff, Christopher (Mohr Siebeck, 2016)
Max Weber argued that a religious group or individual is influenced by all kinds of things but if they claim to be acting in the name of religion, we should attempt to understand their perspective on religious grounds first. He gives religion credit for shaping a person's image of the world, and this image of the world can affect their view of their interests, and ultimately how they decide to take action. For Weber, religion is best understood as it responds to the human need for theodicy and soteriology. He believes that human beings are troubled with the question of theodicy. How can the extraordinary power of a divine god be reconciled with the imperfection of the world that he has created and rules over? People need to know, for example, why there is undeserved good fortune and suffering in the world. Religion offers people soteriological answers, or answers that provide opportunities for salvation - relief from suffering, and reassuring meaning. This volume is a collection of ten articles by Christopher Adair-Toteff that examine the fundamental aspects of Max Weber's sociology of religion. They were published between 2002 and 2015 in various renowned journals and deal with different topics such as charisma, asceticism, mysticism, theodicy, prophets, and "Kulturprotestantismus." In his work, the author attempts to understand, clarify, and interpret key concepts and themes in Weber's sociology of religion.